Paleomagnetism of the Little Dal lavas, Mackenzie Mountains, Northwest Territories, Canada - Morris, W. A.; Aitken, J. D. (Canadian Journal of Earth Sciences, 1982)
The Proterozoic stratigraphic column of the Mackenzie Mountains is dominated by two main successions, the platformal "Mackenzie Mountains Supergroup" beneath, and the Windermere-equivalent Rapitan Group and younger strata, of rift-depression and slope origin, above. The former succession is at least partly older than 770 Ma, the latter younger than 770 Ma. These two main successions are locally separated by an unconformity-bounded succession, the "copper cycle." An important question is whether the copper cycle is more closely related in time and in origin to the older or the younger main succession. Determination of the paleomagnetism of the basaltic lavas locally preserved at the top of the Little Dal Group (top of the Mackenzie Mountains Supergroup) and comparison of their remanence directions with those published for other rocks bearing on the question were thought to be one way of shedding light on this question. Accordingly, paleomagnetic investigation of 10 sites in the Keele River area and six sites in the Thundercloud Range area was undertaken to obtain the remanence direction related to the initial extrusion of the lavas. Coherent directional groupings were only obtained from Little Dal lavas in the Keele River area. Of the three magnetizations found, LD-L (D = 304°, I = 20°, α 95 = 7°) is assumed to represent the magnetization acquired on crystallization of the lavas. If this assumption is correct, the significant difference from the direction LD-A (D = 265°, I = 26°, α 95 = 4°) reported elsewhere for strata low in the Little Dal Group suggests either that the lavas significantly postdate the group or that significant movement of the North American plate occurred during accumulation of the 2 km or so of platformal strata between the lower Little Dal beds and the lavas. The new results presented here also admit the conclusion that the Little Dal lavas do not represent the same igneous events as diabase intrusions dated at about 770 Ma that cut the lower Little Dal.